Guideline for the establishment of climate-smart agriculture multi-stakeholder platforms/forums - Bioversity International and International Center for Tropical Agriculture; Ministry of Agriculture and Livestock Development; Ministry of Agriculture Ethiopia; Kenya Climate Smart-Multistakeholder Platform (2025)
Climate change presents profound challenges to agricultural sustainability, food security, and natural resources, while also offering mitigation opportunities through Climate-Smart Agriculture (CSA). Effective multi-stakeholder collaboration is essential to leverage these opportunities. This guideline provides a practical framework for establishing and maintaining functional Climate-Smart Agriculture Multi-Stakeholder Platforms (CSA-MSPs/Forums) at national or sub-national levels. It outlines core principles, roles, responsibilities, and processes to foster inclusive coordination, knowledge sharing, and evidence-based action among diverse stakeholders. By integrating mechanisms for monitoring, evaluation, and adaptive management, the guidelines aim to support the development of resilient, low-emission agricultural systems and the effective scaling of CSA initiatives.